2009
DOI: 10.1097/bpo.0b013e3181b2842c
|View full text |Cite
|
Sign up to set email alerts
|

A New Classification System Predictive of Complications in Surgically Treated Pediatric Humeral Lateral Condyle Fractures

Abstract: This is the largest series of operatively treated lateral condyle fractures reported in the literature. This classification system and treatment based on fracture displacement and articular congruity predicts the risk of complications, which were more than 3 times as likely to occur in type 3 fractures as type 2 fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
145
0
12

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(164 citation statements)
references
References 14 publications
7
145
0
12
Order By: Relevance
“…The K-wires left protruding outside the skin may increase the possibility of skin infection and the loosening of K-wires [7,14,18]. Weiss et al [23] reported that 3.8% of patients developed skin infection around K-wires and were treated with oral antibiotics. In our study, skin infection around the K-wires occurred in 16.7% of patients, while no patients developed skin infection over cannulated screws.…”
Section: Discussionmentioning
confidence: 99%
“…The K-wires left protruding outside the skin may increase the possibility of skin infection and the loosening of K-wires [7,14,18]. Weiss et al [23] reported that 3.8% of patients developed skin infection around K-wires and were treated with oral antibiotics. In our study, skin infection around the K-wires occurred in 16.7% of patients, while no patients developed skin infection over cannulated screws.…”
Section: Discussionmentioning
confidence: 99%
“…For data analysis purposes, we classified flexion-type injuries as Type 4 fractures. For LC fractures, we used the system proposed by Weiss et al [29] and Wilkins [31] who classified the fractures based on fracture displacement and articular congruity. Type 1 fractures have less than 2 mm of displacement; Type 2 fractures have [ 2 mm displacement and congruity of the articular surface; Type 3 fractures have [ 2 mm of displacement and lack of articular congruity.…”
Section: Methodsmentioning
confidence: 99%
“…11 This is particularly vital to consider because the importance of >2 mm displacement has extrapolated to other fracture sites, including pediatric lateral condylar fractures. 12 Knirk and Jupiter's study also did not include 238 tilt lateral projections, which provide a better visualization of fracture displacement at the distal radius. Additionally, no kappa value was utilized to help determine reviewer error.…”
Section: Discussionmentioning
confidence: 99%